Outcomes of plated metatarsophalangeal joint fusions without transarticular screw fixation - Rana, Parimal; Brennan, Jane; Johnson, Andrea; Owens, Sean; Friedmann, Elizabeth; Spirt, Adrienne; Turcotte, Justin; Keblish, David (Journal of the Foot & Ankle, 2025)
Objective: Evaluate the outcomes of metatarsophalangeal (MTP) arthrodesis performed with plate-only fixation. Methods: A retrospective observational study was conducted on 68 patients submitted to MTP arthrodesis with plate fixation between June 2021 and December 2023. The primary outcome measure was the Patient-Reported Outcomes Measurement Information System (PROMIS) Physical Function (PF) score, evaluated preoperatively and postoperatively in patients who received a locking-compression plate or locking plate. Secondary outcomes included complication rates and the duration of follow-up. Results: The mean patient age was 64.0 years, with a body mass index of 28.5 kg/m2. The minimal clinically important difference of PROMIS-PF scores was achieved by 30.9% of patients. The complication rates were low, with no cases of malunion and only 2 (2.9%) nonunions. Patients who received a locking compression plate had higher postoperative PROMIS-PF scores compared to the locking plate group (46.4 vs. 42.3, p = 0.038), and a greater percentage of these patients experienced improvement in PROMIS-PF postoperatively (71.4% vs. 42.5%, p = 0.035). Conclusions: Both locking-compression and locking plates for MTP joint arthrodesis without transarticular screws are effective, with a low complication rate. These outcomes were comparable to those of prior studies evaluating screw-only and plate and screw fixation constructs. Longer follow-up studies are required to enable direct comparison of outcomes across the alternative arthrodesis techniques. Level of Evidence III; Retrospective, Case-control study.